The reference genome sequence of Artemisia argyi provides insights into secondary metabolism biosynthesis - Gao, Xinqiang; Ma, Qiang; Zhang, Xiaomeng; Wang, Xingyun; Wang, Nuohan; Cui, Yupeng; Li, Shuyan; Ma, Shengming; Wang, Hong; Zhang, Kunpeng (Frontiers in Plant Science, 2024)
Artemisia argyi, a perennial herb of the genus Artemisia in the family Asteraceae, holds significant importance in Chinese traditional medicine, referred to as "Aicao". Here, we report a high-quality reference genome of Artemisia argyi L. cv. beiai, with a genome size up to 4.15 Gb and a contig N50 of 508.96 Kb, produced with third-generation Nanopore sequencing technology. We predicted 147,248 protein-coding genes, with approximately 68.86% of the assembled sequences comprising repetitive elements, primarily long terminal repeat retrotransposons(LTRs). Comparative genomics analysis shows that A. argyi has the highest number of specific gene families with 5121, and much more families with four or more members than the other 6 plant species, which is consistent with its more expanded gene families and fewer contracted gene families. Furthermore, through transcriptome sequencing of A. argyi in response to exogenous MeJA treatment, we have elucidated acquired regulatory insights into MeJA's impact on the phenylpropanoid, flavonoid, and terpenoid biosynthesis pathways of A. argyi. The whole-genome information obtained in this study serves as a valuable resource for delving deeper into the cultivation and molecular breeding of A. argyi.Moreover, it holds promise for enhancing genome assemblies across other members of the Asteraceae family. The identification of key genes establishes a solid groundwork for developing new varieties of Artemisia with elevated concentrations of active compounds.